Europa, Balkan och krigets alltför många offer - Frykman, Jonas; Povrzanovic Frykman, Maja (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2000)
This article discusses the issue of ethnification of violence in Serbia during the 90’s war, beginning with an ethnography by the Dutch anthropologist Mattijs van de Port. From a fieldwork in different Gypsy kafane — pubs or cafes — he has described the role that unreason, wilderness and the lack of civilisation plays in everyday Serbian culture. When the war broke out this culture of unreason was given a privileged site in forming a national identity. Atrocities committed in war could always be referred to as outbursts of a more true Serbian identity. Every effort to anchor war-violence in cultural traditions runs the risk of neglecting the importance of the political and military levels and at the same time underpinning popular stereotypes. There are no general patterns outside of the individual responsibility of politicians, military in command and singular individuals that could be used as explanations. Are certain cultures really more prone to commiting violence than others? Or are most individuals and groups liable to such behaviour at gun’s point? The role that the stereotyped Serb has come to play in the European imagination is today taking over the one previously held by the Turk, being the uncivilised Other.